Impact of nurse-led cardiac rehabilitation on patient's behavioral and physiological parameters after a coronary intervention: A pilot randomized controlled trial - Sriram Premkumar; Lakshmi Ramamoorthy; Ajith A Pillai (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Coronary artery disease, one of the leading causes of mortality and morbidity globally, is a major burden on healthcare resources. Cardiovascular rehabilitation is highly recommended for the early recovery of patients with Ischemic heart disease by improving the functional capacity and decreasing disease progression. A randomized controlled trial was conducted to assess the effect of nurse-led cardiac rehabilitation (CR) on behavioural parameters. MATERIALS AND METHODS: Sixty-two adult patients who underwent percutaneous coronary intervention (PCI) were randomised to two groups to assess the effect of nurse-led cardiac rehabilitation (CR) on behavioural parameters, including adherence to drugs, cardiac diet, lifestyle changes, and selected physiological parameters. The intervention group had nurse-led individualized discharge counseling and clinical follow-up by telephone, whereas the control group received usual care. The comparisons between the control and intervention groups were made using independent Student's t-test or Mann-Whitney U test as appropriate. Pre-test and post-test scores were compared using paired t-test; all tests performed at 5% significance level. RESULTS: Participants in the intervention group presented with moderate to good smoking cessation, improved adherence to drugs (P < 0.0001), physically active lifestyle in 90.3 versus 45.2% (P < 0.0001), adherence to dietary changes, and improved healthcare satisfaction (P < 0.0001). There was also a significant reduction in triglycerides level in the intervention group at 62.51 versus 20.12 mg/dl in the control arm with (P < 0.05), and better controlled physiological indices, including a reduction in systolic blood pressure of 1.54 vs-7.12 mmHg (P = 0.003), bodyweight reduction of 2.48 kg versus-0.09 kg (P < 0.0001) and body mass index of 0.9 versus-0.05 (P < 0.0001). CONCLUSION: Personalised, nurse-led CR significantly improved the participants adherence to healthy lifestyle behaviors and decreased the cardiac risk factors in patients with coronary artery disease.